Integrating Solar Energy and Waste-to-Energy Systems for Urban Renewable Energy Development: A Case Study of Cilegon City, Indonesia - Rizky Ramadhan Marlamsya; Silviana Silviana; Sri Widodo Agung Suedy (Papanda Publisher, 2026)
Indonesia's renewable energy penetration (12.3% in 2022) lags significantly behind 2030 targets (19-23%), with Cilegon City facing 1,167 unelectrified households and rising waste generation. This study assessed renewable energy development potential through LEAP-based electricity demand modeling (2023-2033) and technical-economic evaluation of solar photovoltaic and Refuse-Derived Fuel (RDF) systems. Meteorological and waste generation data informed engineering calculations and financial feasibility analysis. LEAP projections indicate residential electricity demand reaching 728.1 MWh per household by 2033, driven by 13.9% population growth. Off-grid solar PV systems demonstrate viability with Rp. 5,774/kWh levelized cost for unserved households. The proposed UPTD 3 Merak RDF facility shows strong economics: 22 tonnes/day capacity, 2-year payback, Rp. 12.5 billion NPV, and 3.01 benefit-cost ratio. Findings reveal that institutional rather than technical barriers impede deployment, highlighting needs for standardized subsidies, clarified jurisdictional frameworks, and municipal-utility partnerships. This research advances urban renewable energy planning by integrating bottom-up energy modeling with localized assessments, providing replicable frameworks for Indonesian cities pursuing energy transition and environmental sustainability goals.